2018
DOI: 10.1080/01652176.2018.1473660
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR plasma metabolomic profiling of ovarian quiescence in energy balanced postpartum dairy cows

Abstract: As the milk production of dairy cows increases, the reproductive capacity gradually declines. Ovarian quiescence has become one of the concerns of the dairy industry. Objective: To explore the different plasma metabolite levels between estrus and anestrus in energy balanced (EB) dairy cows. Methods: Ten estrous and 10 anestrus EB Holstein cows in early lactation were selected for the study.1 H nuclear magnetic resonance technology was used to detect plasma metabolites and screen different plasma metabolites be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
2
12
0
Order By: Relevance
“…The sample handling was consistent with the 1 H-NMR sample handling method reported earlier ( 1 , 24 , 27 ). Serum samples were adjusted to 99.8% (v/v) D 2 O phosphate buffer solution containing 0.05% (w/v) total suspended particulate (TSP matter: 0.2 M Na 2 HPO, 0.2 M NaH 2 PO 4 , NaH 2 PO 4 ) at pH of 7.0 and centrifuged at 12,000 × g for 20 min at 4°C, and the supernatant was collected into a 5-mm nuclear magnetic tube for testing.…”
Section: Methodssupporting
confidence: 75%
See 3 more Smart Citations
“…The sample handling was consistent with the 1 H-NMR sample handling method reported earlier ( 1 , 24 , 27 ). Serum samples were adjusted to 99.8% (v/v) D 2 O phosphate buffer solution containing 0.05% (w/v) total suspended particulate (TSP matter: 0.2 M Na 2 HPO, 0.2 M NaH 2 PO 4 , NaH 2 PO 4 ) at pH of 7.0 and centrifuged at 12,000 × g for 20 min at 4°C, and the supernatant was collected into a 5-mm nuclear magnetic tube for testing.…”
Section: Methodssupporting
confidence: 75%
“…Method auxiliary identification of peak metabolites was performed on 1 H-NMR spectra. All integrated data were normalized and integrated to perform multivariate statistical analysis as described by Zhang et al ( 1 ) and Hongyou et al ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Some biochemical index such as ALB, ALT, AST, and TP in the plasma might be used to assess the degree of abnormal liver function. 34,[43][44][45] The current study con- injected human recombinant FGF21 to improve the liver lipid metabolism of dairy cows showed that the NEFA content in the plasma of the uninjected control cows did not decrease within 8 days, which was significantly higher than that of the treatment group. Zang 49 added…”
Section: F I G U R Ementioning
confidence: 99%